Enhancing Children's Emotional Skills Through Role-Playing in Group B at KB/TK Negeri Pembina Lembursitu - Siti Rahmi; Nisa Rahayu; Rizki Amelia; Lani Yuningsih; Alya Nursyafiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The objective of this study was to determine whether the use of role-playing could enhance the emotional skills of Group B children at TK Pembina Lembursitu during the 2018/2019 academic year. This study employed Classroom Action Research (CAR) and was conducted at the State KB/TK Pembina Lembursitu during the 2024/2025 academic year, specifically between January and February 2025.The study involved two types of subjects: the subject implementing the action—the Group B teacher at State KB/TK Pembina Lembursitu—and the subjects receiving the action—19 children in Group B. Data were collected through observation, interviews, and documentation. The research instruments included an observation checklist, an interview guide for the teacher, performance indicators, action procedures, and data analysis methods.The study concluded that the role-playing method successfully improved students' emotional skills, as evidenced by the progress observed across Cycle I and Cycle II. Following the intervention in Cycle I, there was an improvement resulting in 48% (9 students) falling into the